Bioactivity of microencapsulated soursop seeds extract on Plutella xylostella - Gomes,Ismael Barros (2016)
ABSTRACT: The aim of this study was to evaluate the bioactivity of microencapsulated extract from the soursop seeds, Annona muricata L. ( Annonaceae ), on diamondback moth, Plutella xylostela L. (Lepidoptera: Plutellidae ). Microencapsulation was performed in a Mini Spray Dryer model B-290 using 50mL of ethanolic and hexanic extracts plus 150mL of ethanol and 150mL of ultrapure water, mixed with aerosil (first polymer) or arabic gum (second polymer). It was possible to microencapsulate the ethanolic extract of soursop seeds only by using the polymer arabic gum at 20%. The microencapsulated extract caused significant acute toxicity (LC50=258mg L-1) and chronic effects, especially reduction of larval viability and increased larval stage. We concluded that the microencapsulation of the ethanolic extract of soursop seeds can be a viable alternative for controlling diamondback moth with possible gains for the environment.